Quantification of Escherichia coli Transfer from Plastic Mulch to Field-grown Tomatoes and Bell Peppers - Autumn R. Burnett; Faith Critzer; Timothy Coolong (Journal of Food Protection)
In the United States, the Food and Drug Administration (USFDA) prohibits the distribution of fruit that is dropped from the plant and contacts the ground during harvest. This includes fruit which contacts the ground while attached to the plant, called “drooping” fruit. In the Southeastern US, tomato and pepper are trellised and grown on plastic mulch. The objective of this study was to obtain bacterial transfer rates from a nonpathogenic Escherichia coli GFP inoculated on plastic mulch (black and white) to fruit (tomatoes and peppers) that contact the ground by being dropped (at heights of 30, 60, or 120 cm) or by drooping (contact times of 1 h or 24 h) in the field during the summer season in Georgia, USA. Plastic mulch was surface inoculated with E. coli (106 CFU/64 cm2), and after drying, populations were reduced by >2–3 log CFU/64 cm2. Once inoculum was dry, the fruit was either dropped from different heights through a PVC pipe or placed back onto the mulch in its initial resting place. The mean log percent transfer of E. coli from plastic mulch to dropped tomato and pepper fruit was −2.00 to 0.46 (0.01–2.88%). Mean log percent transfer rates of E. coli to drooping fruit were between −0.83 and 0.01 (0.15–1.02%), with no significant differences in transfer within crop types between treatments of plastic mulch color or contact time. Field environmental conditions throughout the experiment such as ambient air temperature, relative humidity, UVAB radiation intensity, and surface temperature of plastic likely affected the rates of bacterial transfer. While other studies have evaluated bacterial survival and transfer from mulch to fruit in a laboratory setting, the present study addresses knowledge gaps in bacterial transfer during drooping and dropping incidents in the field when fruit contacts plastic mulch, providing results that have potential to inform future regulatory guidance for produce harvest and handling.